Web based fuzzy diagnosis system and evaluation for five diseases with sort throat symptom - Anbarzadeh, Sadaf; Davari, Hossein (Ciência e Natura, 2015)
Automatic disease diagnosis has been human concern for a long time. Since people are so busy and the doctors visit expenses areso expensive, a lot of different attempts have been done in the field of design of expert system for disease diagnosis. This paper describes aproject work aiming to develop a web based fuzzy expert system for human disease diagnosis. This program models the thinking pattern andhuman activity and leads to close the expert system and human action method. In this paper we have consulted with different physicians andanalyzed the diagnosis procedure and modeled them with a fuzzy expert system. This project is based on development of a web-based clinicaltool designed to improve the quality of the exchange of health information between health care professionals and patients . This system hasbeen tested on five diseases with sort throat symptom such as mononucleosis, scarlet fever, pharyngitis or tonsillitis, common cold and virusinfection and exhibited satisfactory results.